1999
DOI: 10.1099/13500872-145-5-1181
|View full text |Cite
|
Sign up to set email alerts
|

Yersiniabactin from Yersinia pestis: biochemical characterization of the siderophore and its role in iron transport and regulation

Abstract: A siderophore-dependent iron transport system of the pathogenic yersiniae plays a role in the pathogenesis of these organisms. The structure of the yersiniabactin (Ybt) siderophore produced by Yersinia enterocolitica has been elucidated. This paper reports the purification of Ybt from Yersinia pestis and demonstrates that it has the same structure as Ybt from Y. enterocolitica.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
135
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(143 citation statements)
references
References 16 publications
(37 reference statements)
6
135
2
Order By: Relevance
“…The majority of infectious E. coli strains possess multiple systems for ferric ion uptake, notably the relatively lowaffinity aerobactin system and the two high-affinity systems yersiniabactin and enterobactin (Braun, 2003;Perry et al, 1999;Schubert et al, 1998). Our data support the notion that iron-limiting conditions affect biofilm-dwelling E. coli more than their planktonic counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of infectious E. coli strains possess multiple systems for ferric ion uptake, notably the relatively lowaffinity aerobactin system and the two high-affinity systems yersiniabactin and enterobactin (Braun, 2003;Perry et al, 1999;Schubert et al, 1998). Our data support the notion that iron-limiting conditions affect biofilm-dwelling E. coli more than their planktonic counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that YbtA binds, possibly as a dimer, to its promoter target sequences independent of yersiniabactin (10). However, as transcriptional activation is yersiniabactin dependent (249), the interaction of the YbtA-DNA complex with Fe-yersiniabactin was proposed to be a prerequisite for the recruitment of the RNA polymerase complex (9). IrgB, in contrast, is a LysR family-type regulator acting as a transcriptional activator of the Vibrio cholerae IrgA Fe-enterobactin receptor (118).…”
Section: Gene Regulation Of Microbial Iron Homeostasismentioning
confidence: 99%
“…Several siderophores are expressed in K. pneumoniae, including enterobactin, yersiniabactin, salmochelin, and aerobactin, and the roles of these different siderophore molecules in K. pneumoniae infection are discussed in detail below. The affinity of these siderophores for iron ranges from aerobactin with the lowest to enterobactin with the highest (313,314).…”
Section: Siderophoresmentioning
confidence: 99%